Generalization of the modulatory effect of social interaction on personal space - Cui, Shulei; Yang, Tianshu; Liu, Ning (Frontiers in Psychology, 2023)
Personal space (PS) is a safe area around an individual’s body that affects spatial distance when socially interacting with others. Previous studies have shown that social interaction may modulate PS. However, these findings are often confounded by the effects of familiarization. Furthermore, whether the potential regulatory effects of social interaction on PS can be generalized from interacting confederates to strangers remains unclear. To answer these questions, we enrolled 115 participants in a carefully designed experiment. We found that prosocial interaction in the form of a cooperative task effectively reduced PS, and this regulatory effect could be generalized from interacting confederates to non-interacting confederates. These findings deepen our understanding of PS regulation and may be aid in the diagnosis and rehabilitation of dysfunctional social behaviors.